Ear training & sight-singing : a developmental aural skills text - Glen, Ethier (Oxford University Press, 2013)
Designed to provide students with multiple strategies for ear training and sight singing, Ear Training and Sight Singing is a comprehensive series of exercises and techniques in all areas of the practical music discipline. It encompasses aural identification and written transcriptions as well as vocal performance of prepared and sight material. Suitable for use in ear training and sight singing courses for a 4-semester university or college programme anywhere in North America, this introduction provides a clear, logical presentation of the material, beginning with basic elements and progressing carefully through a graduated series of exercises and assignments that guides and monitors student progress. Loaded with practice repertoire, exercises, and assignments, and supported by an audio CD and a wealth of online supplements, Ear Training and Sight Singing provides the ideal one-volume introduction to aural skills that is excellent for student review and study.